The Role of Madrasah Ibtidaiyah in Building Student Characters in The Era Of The 4.0 Industrial Revolution - Niswatun Hasanah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This research aims to understand how the Madrasah's rule of Ibtidaiyah was in shaping the student character of the 4.0 Industrial Revolution era at MI Al-Amin Mataram. In the study it employs a qualitative method. Data obtained from interviews, observations, and documentaries. Research showed that the role of the madrasah character of students is carried on through intracurriculer dan extracurriculer activities. The intracuricular is the teacher inserts the values of character formation in the learning process, such as the Qur'an of Hadist, SKI, fiqih, aqidah morals and Arabic. The method is to integrate fiqh material with character or moral aqeedah with characters and other material that can be integrated with character values. While the extracurricular activities include praying in congregation, praying and delivering the cult every morning, tahfizul Qur’an, tilawatil Qur’an, and hadroh. Through these two types of activities characters will emerge in students which include: religious, being honest, independent, responsible, caring socially, working hard and being able to speak good words. If students have these characteristics, then students will be ready and able to meet challenges in the industrial revolution era 4.0.